Las TIC en el proceso de enseñanza. - Changoluisa Cola, Rosa Matilde (2021)
This research report addresses a problem related to the training needs in Information and Communication Technologies (ICT) of teachers in their teaching practices; The general objective was to analyze the training needs of teachers in the use of ICT in the teaching process of the Sub-levels of Basic, Middle and Higher of the Mariano Negrete Educational Unit. To achieve the objective set, a quantitative approach was applied as a methodology with a non-experimental design and a descriptive level. For data collection, the survey was used as a technique and a questionnaire submitted for expert validation as an instrument. After analyzing the results obtained, it is concluded that the teachers present low knowledge, especially in indicators such as the use of web 2.0 tools such as blog, wikis, podcast as an activity for the subject, use of applications for the creation of augmented reality such as educational resource in the classroom, use of cloud hosting tools to share educational material of the subject, and use of MOOCs as a complementary resource in learning. Based on these inputs, a proposal was made that consisted in the execution of training workshops for the teachers of the educational unit under study. The proposal was validated by three specialists and five users. The silver proposal was intended to strengthen the professional profile of the teachers involved, regarding the use of ICT in the teaching process